A survey of the opinions of state Department of Public Instruction officials concerning the advantages and disadvantages of using minimum competency tests as a criterion for high school graduation - Von Klein, Max Anton (My University, 1982)
The purpose of this study was to determine the opinions of state departments of public instruction officials toward utilizing minimum competency examinations as a criterion for high school graduation. This study also examined procedures used to implement a competency testing program. The following research hypotheses were formulated. 1. What are the opinions of state department of public instruction officials concerning the utilization of minimum competency examinations as one of the criteria for high school graduation? 2. What procedures and processes are employed by state department of public instruction officials in states that have implemented some form of a minimum competency requirement? The current leader of each state department of public instruction was identified. They were the population for this study. A fifty-one item questionnaire was developed to survey the opinions of the state department of public instruction officials concerning the advantages and disadvantages of using minimum competency testing for high school graduation. The instrument was divided into three parts: Part I requested general information about the respondent and his/her state; Part II consisted of opinion statements structured around areas of debate in the use of minimum competency testing; Part III gathered information about the nature of competency testing programs in the states using them. Forty-seven of the original fifty questionnaires were returned, producing a 94% rate of return. Each response on the questionnaire was converted to percentages. A Chi Square test (X2) incorporating the Yates Correction Factor was used to determine if there were significant differences at the .05 level between the expected and observed responses. From analyzing the similarities and differences that were observed in this questionnaire, the following conclusions were made: 1. Respondents believed that current educational practice is inadequate and MCTP is one means to stop the decline in student and school performance. Disagreement exists concerning whether MCT are all that are needed to stop this decline; 2. MCTP were viewed as having some educational use, but the measurement of educational growth was not one of them; 3. The role of state authorities is increasingly taking over evaluation responsibilities that were once the exclusive responsibility of local school districts; 4. Liberal and fine arts programs were not being diminished as a result of MCTP; 5. Because current testing methods do not adequately measure critical thinking and creativity, there is a possibility that these skills will be less emphasized in MCTP; 6. Improper reporting of test results could pose a danger to teachers if scores are used as an indicator of teacher competency; and, 7. MCTP could tend to shift accountability of student failure from the school to the student.
Keywords: Competency-based educational tests -- Public opinion